EXPLORING THE INTERPLAY BETWEEN DIGITALIZATION, CORPORATE GOVERNANCE, AND SDG REPORTING: A PATHWAY TO SUSTAINABLE DEVELOPMENT - ȘTEFANESCU, Cristina Alexandrina (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
This study explores the role of digitalization in advancing sustainable development and its potential to improve SDG reporting. It investigates how digital technologies, along with other macroeconomic factors such as governance, economic, environmental, and social factors, can enhance the quality and effectiveness of sustainability reporting across different countries. Grounded in stakeholder and resilience theory, the research employs OLS regression along with robustness and heterogeneity tests to ensure the reliability and validity of the findings. The study contributes to the literature by highlighting the interconnections between digitalization, corporate governance, and SDG reporting. It also reveals that corporate governance does moderate the relationship between digitalization and SDG reporting. The findings show that countries with higher adoption of digital technologies tend to demonstrate improved sustainability reporting, along with strong performance in environmental health, ecosystem vitality, and economic progress. However, digitalization proves to be a significant driver of SDG reporting in emerging economies but does not have the same effect in advanced countries. From a practical perspective, the study suggests that governments and organizations should prioritize digitalization strategies and governance frameworks to enhance sustainability reporting and better align with the global development goals set out in the 2030 Agenda. JEL classification: Q5, Q01